MAIS INGLÊS MT PROGRAM – INITIAL REFLECTIONS: PROGRAMA MAIS INGLÊS MT – REFLEXÕES INICIAIS (WEB REVISTA SOCIODIALETO, 2025)
The More Inglês MT Program was launched by the State Department of Education of Mato Grosso in 2022, aiming to make the state. The article aims to report how the program works in public schools, analyzing student performance data and comparing it with English language teaching regulations. We used the National Common Curricular Base – BNCC and the Curriculum Reference Document for Mato Grosso (Pedagógico de Língua Foreign) as theoretical support. Authors who discuss continuing teacher education (FREIRE, 2010), (NÓVOA, 2002), (PERRENOUD, 1997) (TARDIF, 2014) will also be used, as well as theorists who deal with English language teaching in a public context (LIMA, 2011).